2014
DOI: 10.1080/00221325.2013.834291
|View full text |Cite
|
Sign up to set email alerts
|

Staying Alone or Getting Attached: Development of the Motivations Toward Romantic Relationships During Adolescence

Abstract: The authors present the initial validation of a romantic relationship motivation scale, enabling the level of self-determined involvement in romantic relationships during adolescence to be examined. The inclusion of Self-Determination Theory (E. L. Deci & R. M. Ryan, 2000) in the motivational constructs enhances the developmental perspective regarding adolescent romantic involvement. The scale was administered to 284 adolescents (163 girls and 121 boys, age 14-19 years) with a self-esteem scale and some questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
11
0
3
Order By: Relevance
“…Romantic experiences during early adolescence (10–14 years), however, can be difficult to study because few young adolescents are engaged in romantic relationships (Carlson & Rose, 2007; Roisman, Booth-LaForce, Cauffman, & Spieker, 2009). Romantic relationship interest and motivation are also low during early adolescence, especially when compared to interest in social status and popularity (Kindelberger & Tsao, 2014; LaFontana & Cillessen, 2010). Yet, there is some indication that other types of romantic experiences, such as crushes (defined as target-specific likings for another person, characterized by one-sided romantic attraction or feelings; Bowker, Spencer, Thomas, & Gyoerkoe, 2012), become increasingly common during early adolescence, with one recent study reporting that 56% percent of young adolescents ( M age = 12.…”
Section: Introductionmentioning
confidence: 99%
“…Romantic experiences during early adolescence (10–14 years), however, can be difficult to study because few young adolescents are engaged in romantic relationships (Carlson & Rose, 2007; Roisman, Booth-LaForce, Cauffman, & Spieker, 2009). Romantic relationship interest and motivation are also low during early adolescence, especially when compared to interest in social status and popularity (Kindelberger & Tsao, 2014; LaFontana & Cillessen, 2010). Yet, there is some indication that other types of romantic experiences, such as crushes (defined as target-specific likings for another person, characterized by one-sided romantic attraction or feelings; Bowker, Spencer, Thomas, & Gyoerkoe, 2012), become increasingly common during early adolescence, with one recent study reporting that 56% percent of young adolescents ( M age = 12.…”
Section: Introductionmentioning
confidence: 99%
“…From this same perspective, Kindelberger and Tsao (2014) highlighted different motivations for engagement in a romantic relationship, which are based on different needs and systems (biological, group membership, attachment, and care). Thus, according to the authors, biological needs could direct the motivation for involvement in romantic relationships in early adolescence.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, according to the authors, biological needs could direct the motivation for involvement in romantic relationships in early adolescence. However, a romantic relationship could also satisfy the group membership system, since the authors showed that one of the leading advantages of being emotionally involved with someone is support and companionship (Kindelberger & Tsao, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies, we expected that boys and girls would differ in their romantic experiences. As girls are driven by intimacy motives and boys by the discovery of erotic practices (Courtois et al, ; Kindelberger & Tsao, ; Zimmer‐Gembeck, Hughes, Kelly, & Connolly, ), girls might report more serious romance whereas boys might report more casual dating. For pending romance, we hypothesized that boys would score higher than girls, because pending romantic experiences—like casual dating—could result from boys' propensity to feel less committed than girls in their relationships (Mallet & Kindelberger, ; Rose & Rudolph, ).…”
Section: Objectivesmentioning
confidence: 99%
“…As explained above, casual dating experience is common during adolescence. Some adolescents see casual and multiple dating as a normative developmental phase stemming from the adolescence process (Kindelberger & Tsao, ). Some authors agree with this view: they consider that a strong emotional involvement in a unique romantic relationship at an early stage may hinder identity clarification, because early committed adolescents would not have explored the different facets of their selves, revealed by the means of a variety of relationships (Samet & Kelly, ).…”
Section: Introductionmentioning
confidence: 99%